2018
DOI: 10.1093/annonc/mdy251
|View full text |Cite
|
Sign up to set email alerts
|

Plasma HPV cell-free DNA monitoring in advanced HPV-associated oropharyngeal cancer

Abstract: Plasma HPV cfDNA monitoring recapitulates fluctuations in disease status. While blood-based HPV DNA monitoring does not currently have a role in managing HPV+ OPC, these data speak to their broad clinical potential in an era of precision medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 22 publications
(24 reference statements)
6
79
0
6
Order By: Relevance
“…According to collection of data/samples, five studies had a prospective design [ 24 , 27 , 28 , 30 , 37 ], whereas four studies were purely retrospective [ 23 , 25 , 29 , 33 ]. Seven studies did not report how data/samples were collected [ 22 , 26 , 31 , 32 , 34 , 35 , 36 ] ( Table 1 , Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to collection of data/samples, five studies had a prospective design [ 24 , 27 , 28 , 30 , 37 ], whereas four studies were purely retrospective [ 23 , 25 , 29 , 33 ]. Seven studies did not report how data/samples were collected [ 22 , 26 , 31 , 32 , 34 , 35 , 36 ] ( Table 1 , Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 27 ] used “HPV16-detect” and compared sensitivity and specificity via real-time PCR. Additionally, eight studies [ 25 , 28 , 29 , 30 , 33 , 35 , 36 , 37 ] used droplet digital PCR (ddPCR). Damerla et al [ 29 ] and Jeannot et al [ 33 ] compared ddPCR with qPCR and they reported more sensitive values by using ddPCR at lower cfHPV-DNA concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of metastatic disease, published longitudinal data is limited. Circulating HPV-DNA levels have been reported in three small studies in HPV-driven cancers to have changes consistent with the disease burden and treatment response 22,32,33 . This is in contrast with the results found in our study, which did not find any correlation between circulating HPV-DNA levels correlating with disease response to treatment.…”
Section: Discussionmentioning
confidence: 95%
“…This is in contrast with the results found in our study, which did not find any correlation between circulating HPV-DNA levels correlating with disease response to treatment. The three published studies used ddPCR to detect circulating HPV-DNA, and included patients with metastatic HPV-driven cervical cancer (n = 19); a case report in metastatic HPV-driven anal cancer (n = 1); and metastatic HPV-OPCSCC (n = 22) 22,32,33 . It is worth noting that these studies all used different definitions of tumor burden measurements to our study; one used RECIST 1.0 criteria, one used immune-related total measurable tumor burden, and one used another novel measurement method to derive the total tumour burden.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when using quantitative reverse transcription PCR to detect HPV16 E6/E7 expression, the presence of circulating HPV16 E6/E7 mRNA at baseline, prior to treatment, was associated with worse progression-free survival and overall survival [56]. This was similarly true of different individual studies, which found that increased levels of pre-treatment HPV16 ctDNA were correlated with worse prognosis [57], and in one study, worse TNM staging as well [58].…”
Section: Circulating Hpv Dna As a Biomarkermentioning
confidence: 97%